Importance of core and linear marsh elements for wetland arthropod diversity in an agricultural landscape. Issue 4 (2nd February 2015) - Decleer, Kris; Maes, Dirk; Van Calster, Hans; Jansen, Ivy; Pollet, Marc; Dekoninck, Wouter; Baert, Léon; Grootaert, Patrick; Van Diggelen, Rudy; Bonte, Dries; R. Leather, Simon; Hassall, Christopher
Abstract The importance of linear habitat elements connecting core habitat patches for biodiversity conservation is still poorly understood. We surveyed reed strips along drainage ditches and reed marshes in an agricultural landscape to assess how both the density of linear habitat elements and the area of core habitat affect diversity and community composition of spiders, ground beetles, and long‐legged flies. For each taxonomic group, species composition of both 'all' and 'typical wetland' species, but not species richness was different between ditches and marshes. Overall local species richness and richness of species of conservation interest were affected at a landscape scale both by the density of ditches and by the area of core wetland. Strength and direction of these effects differed among groups. An increase in the density of reed ditches positively affected the total species richness of spiders and ground beetles and the species richness of typical wetland ground beetles, but not for long‐legged flies and typical wetland spiders. The positive effects were explained by improved network functionality, rather than by increase in available habitat area at landscape level. The number of red list spiders and long‐legged flies increased only with increasing core wetland area, while no significant effects were found for the number of red list ground beetles. Our study revealed that preserving or increasing the density of habitat corridors (more reed ditches) can be beneficial for the species richness of particular predatory arthropods, including species of conservation concern (especially ground beetles). Other groups react indifferently or are only positively impacted by an increase of core wetland area.